Green Accounting, Kinerja Lingkungan, dan Sustainability Report sebagai Determinan Nilai Perusahaan - Dassaad Dassaad; Ananda Nur Fauziah; Riyanti Riyanti; Bertilia Lina Kusrina; Dyah Palupi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Climate change, environmental pollution, and the excessive exploitation of natural resources have become major global issues. Environmental concerns require companies to commit to environmental costs and social aspects within their operational strategies in order to create value for consumers and build stakeholder trust. The food and beverage industry is one of the subsectors that contributes to environmental problems. With its significant economic contribution and substantial environmental challenges, the food and beverage industry needs to develop business strategies focused on sustainability. This study aims to examine the effect of green accounting, environmental performance, and sustainability reports on the firm value of food and beverage subsector companies listed on the Stock Exchange during the 2019–2023 period. The quantitative data used in this study include environmental performance as measured by PROPER, sustainability reports, and annual reports of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample consisted of 9 companies selected through a purposive sampling method, with a total of 45 observations over 5 years. Data testing was conducted using multiple regression analysis with the assistance of SPSS version 30 software. The results of this study indicate that green accounting has no effect on firm value. Meanwhile, environmental performance and sustainability reports have a negative effect on firm value. These findings suggest that green accounting practices and sustainability disclosures have not yet become major considerations for investors, who still tend to focus on short-term financial performance.